DAMPAK VOUCHER GRATIS ONGKOS KIRIM DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN ONLINE PADA SHOPEE - intisarih Haryanti (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
The aim of this research is to determine and analyze the influence of free shipping coupons and online customer reviews on shopee online purchasing decisions. This research uses associative research using quantitative data from primary data sources. The research instrument used in this research is a Likert scale questionnaire. Population used in this research were all Shopee users in the city of Bima whose exact number is unknown (unknown population). Because the population is not known with certainty, the Cochrane formula was used to determine the sample size for the unknown population, resulting in a sample of 96 people. The data collection techniques used were observation, questionnaires, and literature review. The data analysis techniques used were validity tests, reliability tests, classical assumption tests (normality tests, multicollinearity tests, autocorrelation tests, heteroscedasticity tests), multiple linear regression analysis, correlation coefficients. multiple, decision test, f test, and t test. The findings show that comfort and trust influence online purchasing decisions (the case study uses Shopee with a strong relationship, the magnitude of the influence is 0.372 or 37.2%, and the remaining is 62, 8% is influenced by other factors not examined in this study.